Migrant Entrepreneurs in East Indonesia: A Schumpeterian Perspective - C. Gorter (Tinbergen Institute, 2000)
Entrepreneurship is at the heart of Schumpeterian theory. Potential entrepreneurs donot only take risk by seeking for new investment opportunities or new products, butalso by choosing new markets or new locations. Firm migration is thus an importantcomponent of modern entrepreneurship. Spatial (re-)location of firms may also be acombination of economic motives and socio-cultural determinants. This paper aims tooutline the strategic economic considerations of firms and to introduce a model forprofit seeking behaviour of entrepreneurial migrants, governed by multiple economicand socio-cultural motives. This framework is empirically tested by means of anextensive case study for ethnic migration decision of firms in East Nusa Tenggara, aperipheral region in East Indonesia.
Keywords: 330; Entrepreneurship-Ansatz; Kleine Sundainseln; Migranten